True or False Questions on Students’ Reading Ability - Effrina Yuricki (LPPM STKIP PGRI Bandar Lampung, 2024)
True or False Questions are the most familiar question type, and it is widely used in testing. The objective of this research is to determine whether or not the True or False Question strategy can improve students' reading ability. Based on the preliminary research at the tenth class of SMA Negeri 1 Punduh Pedada, the writer found that students got difficulties reading especially in reading narrative text. They have problems finding the main idea of the text and comprehending the text. True or False Question is believed can improve their reading ability. In this research, the writer used the experimental method and the population of this research was 238 students in 6 classes. The sample in this research was taken by using the cluster random sampling technique. In the data collecting technique, it was used a written test, the writer gives a test reading test sheet. The kind of test is multiple choice which consists of 40 items, each item consists of five options: A, B, C, D, and E. The point of each item is 2,5. The data analysis by using the t-test formula with the distribution with dk=78 obtained t-table= 0.05 or a significance level of 5% was equal to 1.67 and t-table= 0.01 or a significance level of 1% was equal to 2.39 and t-test= 3.27, it means that t-test was higher than t-table with the significance level 5% and 1% (3.27>1.67), (3.27>2.39). The average score of students' reading ability in the experimental class who were taught by using True or False Questions was higher than students in the control class who used the conventional teaching technique (78.21 was higher than 72.12). Therefore, the writer concluded that a True or False Question was able to increase students' reading ability and activity.